Effectiveness of Women's Empowerment Series in Increasing Stunting Literacy Relating to Oral Health Maintenance (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
The high incidence of stunting necessitates accelerated prevention programs, which can be implemented by enhancing stunting literacy as part of women's empowerment initiative to prevent stunting, particularly in the field of oral health. Stunted children are more susceptible to dental caries due to changes in saliva characteristics, such as reduced flow rate and pH. The objective of this empowerment program is to increase women's literacy regarding stunting, specifically related to oral health and nutrition. The method includes a series of community empowerment activities through five educational programs and two training programs aimed at improving literacy in stunting, oral health, and nutrition. This is followed by demonstrations to enhance the skills of women cadres using educational units and training modules, which have been validated by public health experts. The results of the empowerment program indicate a significant increase in knowledge and skills within the community, reaching optimal levels, although the degree of improvement varies and there remains room for further development. The program, which empowers women by increase literacy on stunting and its relation to oral health and nutrition through education and training, can contribute to improving overall oral health literacy.